INNOVATIVE-PEDAGOGICAL FACTORS OF ANALYTICAL THINKING DEVELOPMENT IN FUTURE ECONOMISTS (Scientific journal of the Fergana State University, 2023)
The article analyzes the modern pedagogical conditions, factors, stages, components, methods of developing analytical thinking in future economists. Also, the article examines the pedagogical-hierarchical system of analytical thinking skills, forms of manifestation in future economists.